Effects of hospital-based pulmonary rehabilitation in acute exacerbations of COPD - Vieira, Marta Sofia de Almeida (2019)
Background: Pulmonary rehabilitation (PR) has grade A of recommendation for patients with stable chronic obstructive pulmonary disease (COPD). However, the effect of PR in hospitalised patients with acute exacerbation of COPD (AECOPD) is still controversial. Aim: To contribute for determining the effects of PR in hospitalised patients with AECOPD. Methods: A pre-post intervention pilot study was conducted in the Centro Hospitalar de Leiria. Patients were evaluated 24-48 hours after clinical stabilisation (baseline) and at discharge. The following information was collected: respiratory rate by observation, heart rate and oxygen saturation with an oximeter, blood pressure (BP) with a sphygmomanometer, dyspnoea with the modified Medical Research Council dyspnoea questionnaire (mMRC), dyspnoea and fatigue at rest with modified Borg scale (mBorg), the impact of the disease with the COPD Assessment test (CAT), handgrip and quadriceps muscle strength with dynamometers, respiratory muscle strength with respiratory pressure meter, functionality with Short Physical Performance Battery (SPPB) and exercise tolerance with 1-minute sit-to-stand test (1’STST). A PR programme composed of breathing retraining and airway clearance techniques, exercise training and psychoeducational support (delivery of flyers with important information: breathing control and positions for dyspnoea relief, airway clearance techniques, lower respiratory tract infections and exercise), was implemented 5 days per week during hospitalisation. Three months after discharge, rehospitalisations and visits to the emergency service were noted. Comparisons between baseline and discharge were performed with the Wilcoxon signed-rank tests, effect sizes (ES) were calculated and whenever possible, the number and percentage of patients that improved above the minimal clinically important difference (MCID) was determined. Results: Fifteen inpatients diagnosed with AECOPD [14 male; 71.2±7.2y; 46.1±20.6% of predicted of forced expiratory volume in one second (FEV1)] were enrolled. Patients were hospitalised 13±4.3 days and concluded 4,7±2 sessions of PR. After discharge, significant improvements were found in dyspnoea at rest (ES=-0.976, p=0.008), BP (systolic BP, ES=-1.584, p=0.016; diastolic BP, ES=-1.231, p=0.008) and CAT (ES=-0.925, p=0.01). No significant differences were found in the remaining outcome measures. Most of the outcome measures improved in at least 50% of the patients. Improvements above the MCID were observed in 8 (80%) patients on dyspnoea at rest assessed with the mBorg, 7 (70%) on the CAT, 6 (60%) on the mMRC, 6 (60%) on the 1’STST and 5 (50%) on SPPB total score. No adverse events were reported. Three months after discharge, 6 patients visited the emergency service and of these 6, 4 were hospitalised due to a re-exacerbation of the COPD. Conclusions: Hospital-based PR seems to be a safe and effective intervention in patients with an AECOPD. Nonetheless, since approximately 40% of the patients required health services within 3 months of follow-up, it becomes clear that support of these patients needs to be continued in the community to minimise the necessity to resort to hospitals. This study provided similar improvements to the already recognised benefits of PR in stable patients with COPD, nevertheless studies with more robust methodologies are needed to confirm these results.